Pengaruh Current Ratio dan Debt to Asset Ratio Terhadap Return on Assets Pada PT Semen Baturaja (Persero) TBK Tahun 2014-2023 - Rosmalini, Hikmah; Zaman, Muhamad Badru (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine whether there is an influence between the Current Ratio and Debt to Asset Ratio on Return On Assets at PT Semen Baturaja (Persero) Tbk from 2014 to 2023, both partially and simultaneously. This study uses secondary data obtained from the annual financial reports of PT Semen Baturaja (Persero) Tbk for the years 2014-2023. This study is a descriptive analysis using a quantitative approach. The data collection technique in this study uses classical assumption tests, including normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The data analysis technique in this study uses multiple linear regression analysis processed using Eviews version 12. Based on the partial results of the study, the Current Ratio does not have a significant effect on Return On Assets, with a t-statistic value smaller than the t-table value, namely -1.142922 2.36462, and a significance value of 0.2906 0.05. The Debt to Asset Ratio also has a significant effect on Return On Assets with a t-statistic value greater than the t-table value, namely -4.918384 2.36462 and a significance value of 0.0017 0.05. Simultaneously, the Current Ratio and Debt to Asset Ratio have a positive and significant effect on Return On Assets with an F-statistic value greater than the F-table value, namely 66.19018 4.74 and a significance value of 0.000028 0.05. R-squared 0.935428 Current Ratio and Debt to Asset Ratio affect Return On Asset by 93.54%, with the remaining 4.1% affected by other variables.